Pengaruh Opini Audit, Temuan Audit Dan Tindak Lanjut Hasil Audit Terhadap Jumlah Kasus Korupsi - Fransisca Listyaningsih Utami (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
The increase in the number of regional governments that have received the unqualified predicate in their regional financial reports is not in line with the criminal acts of corruption cases that have occurred in a number of regions. In fact, not a few regional heads were involved in the corruption crime. Seeing this phenomenon, this study aims to analyze the effect of audit opinions, audit findings and audit corrections on corruption cases in local governments in Indonesia in 2012-2017. This research is a quantitative study using panel data and multiple regression with a random effect model. The results showed that audit opinion and audit findings on regulatory compliance had a negative effect on corruption cases, audit rectification had a positive effect on corruption cases. However, audit findings regarding weaknesses in the internal control system have no effect on corruption cases.